Characterization of the early cellular immune response induced by HPV vaccines - Pasmans, Hella; Berkowska, Magdalena A.; Diks, Annieck M.; de Mooij, Bas; Groenland, Rick J.; de Rond, Lia; Nicolaie, M. Alina; van der Burg, Sjoerd H.; van Dongen, Jacques J. M.; van der Klis, Fiona R. M.; Buisman, Anne-Marie (Frontiers in Immunology, 2022)
Abstract Introduction Current human papillomavirus (HPV) vaccines consist of virus-like particles (VLPs) which are based on the L1 protein, but they are produced by different expression systems and use different adjuvants. We performed in-depth immunophenotyping of multiple innate and adaptive immune cells after vaccination with bivalent versus nonavalent HPV vaccines. Method Twenty pre-menopausal HPV-seronegative women were enrolled and randomized to receive three-doses of either the bivalent or the nonavalent HPV vaccine. Blood samples were collected at multiple time points from baseline up to 7 months after first vaccination. Four extensive EuroFlow flow cytometry antibody panels were used to monitor various immune cell subsets. Additionally, HPV-specific memory B- and T cells were determined by ELISPOT and HPV-specific antibody levels were measured by a VLP-based multiplex immunoassay. Results In both cohorts, the numbers of plasma cells expanded in the first week after both primary and tertiary vaccination. HPV16 and HPV18-specific antibody levels and memory B and T-cell responses were higher in the bivalent than in the nonavalent vaccinees one month post third vaccination. For HPV31 and HPV45-specific antibody levels this pattern was reversed. Monocytes showed an expansion one day after vaccination in both cohorts but were significantly higher in the bivalent vaccine cohort. Large heterogeneity in responses of the other cell subsets was observed between donors. Conclusion This pilot study showed a consistent response of monocytes and plasma cells after vaccination and a considerable variation in other circulating immune cells in both types of HPV vaccines between donors.